Mengoptimalkan Pengalaman Belanja dengan Aplikasi E-Commerce - Ririn Razina; Alya Yunita; Khoiru Sabilah (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The shopping experience through e-commerce applications is now increasingly the main choice of consumers in the digital era. This article discusses approaches and strategies to optimize the user shopping experience on e-commerce platforms. User experience optimization is carried out through various aspects, such as personalization, ease of navigation, transaction security, and the integration of technologies such as artificial intelligence (AI) and data-driven recommendations. By providing a more personalized and efficient shopping experience, e-commerce applications are expected to increase customer loyalty, increase conversions, and strengthen competitiveness in an increasingly competitive market. Technology implementation recommendations and intuitive interface design are included to provide practical guidance for e-commerce app developers. Qualitative methods are research approaches that focus more on an in-depth understanding of the various aspects and contexts involved in a phenomenon. In the context of Optimizing the shopping experience with e-commerce apps, qualitative methods can help you understand social factors, consumer behavior, and issues that may not be visible in quantitative data. The qualitative method will help with an in-depth understanding of how to optimize the shopping experience with e-commerce apps and understand qualitative aspects that may not be seen in quantitative research.